2021
DOI: 10.1177/08902070211005621
|View full text |Cite
|
Sign up to set email alerts
|

Person-situation dynamics in educational contexts: A self- and other-rated experience sampling study of teachers’ states, traits, and situations

Abstract: The situations people find themselves in and how they experience them is fundamental to a host of life and work outcomes. However, most research has so far only relied on self-reports and is thus not able to disentangle different situation components. The present study therefore examined the dynamics between self- and other-rated situation characteristics, personality traits, and personality states in an educational setting. One hundred and seventy-three student teachers ( n = 2244–2261 observations) and 94 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 90 publications
4
22
0
Order By: Relevance
“…These findings suggest a low convergence between two conceptualizations of personality traits (i.e., average tendencies vs. contingencies), as measured here. This is in line with previous empirical work suggesting the scarcity of interaction effects with this kind of data (e.g., Abrahams et al, 2021; Sherman et al, 2015; Sherman & Pashler, 2019; Wilt & Revelle, 2019; cf. Breil et al, 2019; Quintus et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These findings suggest a low convergence between two conceptualizations of personality traits (i.e., average tendencies vs. contingencies), as measured here. This is in line with previous empirical work suggesting the scarcity of interaction effects with this kind of data (e.g., Abrahams et al, 2021; Sherman et al, 2015; Sherman & Pashler, 2019; Wilt & Revelle, 2019; cf. Breil et al, 2019; Quintus et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…These findings on average contingencies were replicated by further studies (e.g., Abrahams et al, 2021;Horstmann et al, 2021a;Quintus et al, 2021). Some studies reported associations between individual differences in contingencies and personality trait variables (i.e., crosslevel interactions, e.g., Breil et al, 2019;Quintus et al, 2021), but others reported few significant interaction effects (e.g., Abrahams et al, 2021;Sherman et al, 2015). Zooming in on specific contingencies in the work context, Beckmann et al (2021) were among the first to examine the stability of individual differences in situational contingencies, reporting some long-term stability of task-contingent Conscientiousness and Neuroticism.…”
Section: Previous Empirical Work On Contingenciessupporting
confidence: 64%
See 3 more Smart Citations